Ekopesantren: An Ecology-Based Education Model with Local Wisdom Supports the Sustainable Development Goal's - Muhamad Taufik Bintang Kejora; Aan Komariah; Endang Herawan; Asep Sudarsyah (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates an ecology-based education model incorporating local wisdom to support Sustainable Development Goals (SDGs) in Islamic boarding schools (pesantren). The research focuses on Al-Ashriyyah Nurul Iman Islamic Boarding School in Bogor, Indonesia, examining its approach to sustainability within an Islamic educational framework. A qualitative research approach was employed, utilizing semi-structured interviews, observations, and document analysis. Informants included school leaders, students, teachers, staff, the eco-pesantren team, and the surrounding community. Data were analyzed using qualitative descriptive techniques and triangulation to ensure reliability. Findings indicate that Al-Ashriyyah Nurul Iman Ecopesantren integrates Islamic values, local wisdom, and sustainability principles through a holistic educational model. This includes an environment-based curriculum, inclusive community engagement, eco-friendly campus management, a sustainability culture, and circular economy practices. The pesantren applies local wisdom values such as silih asih (mutual care) and reciprocal nurturing, positioning students as key agents of sustainable transformation. Through circular economy initiatives, students actively contribute to sustainability by converting waste into productive resources. These efforts align with multiple SDGs, including SDG1 (No Poverty), SDG2 (Zero Hunger), SDG3 (Good Health and Well-being), SDG4 (Quality Education), SDG5 (Gender Equality), SDG6 (Clean Water and Sanitation), SDG7 (Affordable and Clean Energy), SDG13 (Climate Action), and SDG17 (Partnerships for the Goals). The integration of ecological education and local wisdom in Islamic boarding schools fosters sustainability and enhances student participation in achieving SDGs, demonstrating the potential of pesantren as models for sustainable education.